Rola nauczyciela edukacji wczesnoszkolnej w niwelowaniu stresu związanego z podjęciem nauki szkolnej przez dzieci 6-letnie - Musiał, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The younger school age is one of the critical moments in terms of experiencing stress. Due to the transition from pre-school to school environment, increased learning requirements, progressive competency acquisition (reading, writing, counting), reduced fun activities. Going to school is social ennoblement, but it can not be forgotten that this new situation puts children in the need to enter into diverse interactions in the classroom, school, peers, teachers and other school staff, and with the same As a pupil is staying in a group for extended moments of time requires a classroom activity is a difficult task for a small children. There are many problems that he can not always cope with. For this reason, it is experiencing increased stress. Symptoms of stress in children are varied, especially stress manifested by physiological, behavioral (emotional, behavioral) and cognitive symptoms. Individualization of work with a six-year-old minimizes the negative effects of exceeding the school threshold, decreases the level of stress experienced by the child. In addition, stimulating the development of a small pupil, through his subjective treatment, directly leads to the creation of conditions in the school space in which the child as an active and creative individual has the opportunity to meet his or her needs.
Keywords: child; school education; stress adaptation; teacher